Comparative phylogeography of two symbiotic dorvilleid polychaetes (Iphitime cuenoti and Ophryotrocha mediterranea) with contrasting host and bathymetric patterns. Issue 1 (9th July 2016) - Lattig, Patricia; Muñoz, Isabel; Martin, Daniel; Abelló, Pere; Machordom, Annie
Abstract: Two symbiotic polychaetes living in brachyuran crabs in the western Mediterranean and the nearby eastern Atlantic, Iphitime cuenoti and Ophryotrocha mediterranea, were analysed to determine their phylogeographical patterns and the possible effects of known oceanographic barriers in the study area. The analysed species live in hosts inhabiting well-differentiated depths, a factor that may be crucial for understanding the different patterns observed in each species. Iphitime cuenoti was found in four different host crabs between 100 and 600 m depth and showed some level of genetic homogeneity, reflected in a star-like haplotype network. Furthermore, barrier effects were not observed. By contrast, O. mediterranea was exclusively found in a single host crab species living between 600 and 1200 m depth. Phylogeographical analyses showed two lineages that pre-date the existence of current barriers. The geological history of the study area, including the most recent glaciation events, probably led to a secondary contact between the lineages, thus forming a single metapopulation. The phylogeographical pattern found in each species may be explained by differences in dispersal ability, habitat, and host crab specificity that have led them to be differentially affected by historical events. This study is the first to use a phylogeographical approach on symbiotic polychaetes.